Enhancing Resilience in Community-Dwelling Older Adults: A Rapid Review of the Evidence and Implications for Public Health Practitioners - Madsen, Wendy; Ambrens, Meghan; Ohl, Melanie (Frontiers in Public Health, 2019)
Background: Resilience is a valuable platform for strengthening individuals and communities in the face of disaster. This review sought to evaluate the current literature related to individual and community resilience in community-dwelling older adults to understand the status of resilience in this population, identify gaps, and make recommendations about effective interventions that promote improved individual and community level capacity. Recognizing the concept of resilience is contested, the review conceptualized resilience as a collective concept that is multi-level and interdependent across those levels, cumulative, and contingent on context. Methods: The rapid review located 29 relevant peer review journal articles and industry reports related to research or evaluations of interventions aimed at increasing resilience at either a personal or community level. The results of these papers were thematically analyzed. Results: This review found personal resilience relates to those personal capacities and resources one has and uses to deal with individual stresses and change. We identified several recurring themes within those studies focused on personal resilience, including: (1) positive reframing and agency; (2) personal meaning and purpose; (3) acceptance and belonging. At a community level, we identified the following themes influence collective capacity and resources: (1) empowerment and shared decision making; (2) collective agency; and (3) collective leadership and engagement. Conclusions: The review highlighted the need to reframe how communities view older adults and shift the narrative away from focusing on age-related deficits toward acknowledging the economic and social contribution older adults make to the community through activities such as volunteering and the sharing of knowledge of history, culture and skills. Demonstrating the interdependence across levels, these activities illustrate personal-level capacities promoting collective action and participation as important for increasing community resilience. The review argues resilience is developed in everyday circumstances, therefore active involvement within communities needs to be encouraged within community-dwelling older adults. Developing active involvement will not only contribute to both personal and community level resilience but will enable communities to prosper and flourish through adversity.